Determination of isotopic ratio of сalcium by gamma activation analysis and free radical oxidation of lipids in normal and cancerous tissues of thyroid gland - Dikiy, N.P.; Dovbnya, A.N.; Меdvedeva, Е.P.; Khizhnyak, N.A.; Uvarov, V.L.; Khizhnyak, A.A.; Krasnoselsky, N.V. (Вопросы атомной науки и техники, 2000)
Chemiluminescence and gamma activation analysis was used to determine the isotopic ratio of calcium in normal, non-malignant and cancerous tissues of thyroid gland. This result was used for diagnostics of cancerous thyroid gland morbidity. The high value of isotopic ratio ⁴⁴Ca/⁴⁸Ca in paratumor tissues of thyroid gland has allowed concluding about significance of transmembrane circulation calcium.